Strengthening Parental Participation through School-Community-Parents Partnership in the G7KAIH Habituation Journal - Masayu Rindang Bayu Kencana; Erny Roesminingsih; Nuphanudin Nuphanudin (Yayasan Darussalam Bengkulu, 2026)
This research aims to analyze the partnership communication strategy between the school and parents in supporting the G7KAIH Habituation Journal program at KB TK Cita Mandiri. The main objective is to create an adaptive communication strategy model to shift the role of parents from mere information recipients to active partners in their children's education. This study employs a qualitative design with a case study approach. Informant selection was conducted purposively, involving the school principal, teachers, school committee, parents, and external partners. Data collection was carried out through in-depth interviews and participatory observation, then analyzed using an interactive model (data condensation, data display, and drawing conclusions) along with triangulation and member checking to ensure data validity. The results indicate that low parental participation is often caused by time constraints and unclear instructions (roles). To overcome this, implementing two-way communication through digital platforms such as WhatsApp becomes an effective solution, provided it is supported by instructional communication that is clear, easy to understand, has detailed directions, and provides room for questions and answers. In conclusion, the planned and responsive utilization of communication technology serves not only as a means of delivering information but also as a measuring tool for learning continuity capable of bridging the gap in parental participation and forming a sustainable partnership ecosystem at the early childhood education (PAUD) level.